The warrior heir - Chima, Cinda Williams (New York : Hyperion Books for Children, 2006)
After learning about his magical ancestry and his own warrior powers, sixteen-year-old Jack embarks on a training program to fight enemy wizards.
Accelerated Reader AR
Keywords: Magic -- Juvenile fiction; Wizards -- Juvenile fiction; Identity (Philosophical concept) -- Juvenile fiction; Fantasy fiction